An Endogenous Mammalian Retinoid X Receptor Ligand, At Last!. (6th May 2016) - de Lera, Ángel R.; Krezel, Wojciech; Rühl, Ralph
Abstract: 9‐ cis ‐Retinoic acid was identified and claimed to be the endogenous ligand of the retinoid X receptors (RXRs) in 1992. Since then, the endogenous presence of this compound has never been rigorously confirmed. Instead, concerns have been raised by other groups that have reported that 9‐ cis ‐retinoic acid is undetectable or that its presence occurs at very low levels. Furthermore, these low levels could not satisfactorily explain the physiological activation of RXR. Alternative ligands, among them various lipids, have also been identified, but also did not fulfill criteria for rigorous endogenous relevance, and their consideration as bona fide endogenous mammalian RXR ligand has likewise been questioned. Recently, novel studies claim that the saturated analogue 9‐ cis ‐13, 14‐dihydroretinoic acid functions as an endogenous physiologically relevant mammalian RXR ligand. Abstract : Receptive to feedback : 9‐ cis ‐13, 14‐Dihydroretinoic acid may be the first endogenous physiologically relevant mammalian retinoid X receptor (RXR) ligand. It binds to and activates RXR, displays biological activities similar to those of synthetic RXR agonists, and coordinates the transcriptional activities of several nuclear receptor signaling pathways, possibly through the corresponding permissive heterodimers.